Language, Literature and African Common Norms (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2024)
The basic function of language is communication and its users subconsciously protect its expensive capabilities. It helps in cultural transmission and each generation uses the form of language handed down by the previous generation, language is usually adapted and altered to suit the personal requirements of the next generation. Similarly, a distinctive form of language can give a cultural group a sense of identity, uniting insiders and alienating outsides. The situation in most parts of Africa supports scholars’ argument that for any group of people to share a sense of common norm, a certain minimum level of communication between them must be guaranteed. And the incontrovertible evidence shows that language has remained one of the most visible and enduring senses of that shared identity. In Africa, evident shows that language has become a very strong factor for ethno-national identity, with the ethnic loyalty overriding national interests. Previous scholarly contributions on the complex linguistic situation in Africa have discussed strategies adopted in language planning and types of language policies in many of the nations in Africa. Drawing on these contributions, as well as incorporating recent developments, this article language, literature and African common norms discusses aspects of language, literature, and African common norms and how they affect Africa. It examines language as power, norms of Africa, African literature and the importance of language in African society. The study adopts a qualitative descriptive method and uses Dell Hymes (1966) communicative competence theory. The findings show that the study of language, literature and African common norms has really contributed a lot in Africa. The study recommends that African norms should be maintained through teaching and exposing our children to them as early as possible so that it can become part of their way of living.
Keywords: Language, Literature, Common, Norm, Africa